2018
DOI: 10.1590/1518-8345.2316.3049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the board game as educational technology on schoolchildren’s knowledge on breastfeeding

Abstract: Objective:to evaluate the effect of the board game as an educational technology on schoolchildren’s knowledge on breastfeeding. Method:cluster-randomized clinical trial, held in nine schools, with 99 children in the third grade of elementary school (control group = 51 and intervention group = 48). The pretest was conducted in both groups; intervention consisted in the application of the educational technology immediately after pretest to the intervention group; and the post-test was applied on the 7th and 30th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
(50 reference statements)
0
10
0
6
Order By: Relevance
“…Other studies (17)(18)(19)(20)(21)(22)(23)(24)(25) that used technologies as health education strategies reinforce evidence of innovations in BF assistance, such as: use of educational games, electronic media, educational manuals, information booklets, video conferencing, and digital instant messaging.…”
Section: Discussionmentioning
confidence: 89%
“…Other studies (17)(18)(19)(20)(21)(22)(23)(24)(25) that used technologies as health education strategies reinforce evidence of innovations in BF assistance, such as: use of educational games, electronic media, educational manuals, information booklets, video conferencing, and digital instant messaging.…”
Section: Discussionmentioning
confidence: 89%
“…At the second stage, the players complete a mix and match game by matching characters, such as a bully, a victim, a reinforcer, or a defender and their roles in a bullying incident. The third stage is a collaborative game in which the players need to work together to accomplish their training tasks.Participants were 328 students (11–12 years old).The game-only group: n = 116.The game-with-debriefing group: n = 125.The control group: n = 87.The game-only group played the Galaxy Rescuers game.The game-with-debriefing group played the Galaxy Rescuers game and conducted reflection and discussion.The control group conducted regular bulling curriculum using conventional teaching methods, such as antibullying videos and worksheet assignments.The Galaxy Rescuers game significantly increased players’ knowledge about bullying.The game-with-debriefing group showed a larger increase in bullying knowledge than the game-only group.The game-with-debriefing group also showed a change in bullying attitude and empathy.Unable to calculateUnable to calculateMartins et al (2018) [18]cRCTThe board game educational intervention “Trilha Família Amamenta” (Breastfeeding Family’s Trail).Participants were 171 children in the third grade of elementary school. Analyzed participants were 99.The intervention group: n = 51, post-assessment after 30th: n = 48.The control group: n = 56, post-assessment after 30th: n = 51.The intervention group: children participated in the educational intervention with the board game.The control group: children did not participate in the educational intervention with the board game.Scores for knowledge on breastfeeding were higher in the intervention group, on the 7th and 30th, than the control group.Within the intervention group, there was a significant increase of the means of scores for knowledge on breastfeeding in the posttest for the 30th day.d = 1.50 (between pre and post test at the 7th day) on Breastfeeding Knowledge.d = 1.81 (between pre and post test at the 30th day) on Breastfeeding Knowledge.d = 0.81 (between the mean gain of the intervention group and the control group at the 7th day) on Breastfeeding Knowledge.d = 0.93 (between the mean gain of the intervention group and the control group at the 30th day) on Breastfeeding Knowledge.Viggiano et al (2018) [19]cRCTThe board game “Kaledo”: it is a new educational board game to improve nutrition knowledge and to promote a healthy lifestyle.…”
Section: Resultsmentioning
confidence: 99%
“…According to Charlier and De Fraine [22], board games can be an enjoyable and motivational method for learning content and enhancing group interactions, competition, and fun. Martins et al [18] reported that board games teach educational content in a playful and enjoyable way and involve interactions with family and friends; thus, they favor knowledge acquisition by enabling exchanges of experiences and learning. Furthermore, Wanyama et al [16] showed that, as a method of health education, board games increase the acquisition of knowledge as well as result in more positive experiences than do health talks among both participants and facilitators.…”
Section: Resultsmentioning
confidence: 99%
“…No panorama nacional, apenas 9,3% das crianças são amamentadas exclusivamente (3) , o que sugere a necessidade de pensar em intervenções educativas para melhora desse quadro em fases iniciais da vida, como a fase escolar, além de intervir em diversos cenários, a exemplo da família e o ambiente escolar (4) .…”
Section: Introdução Sunclassified
“…Nota-se, então, que é incipiente o planejamento e consolidação de estratégias educacionais que possam promover o conhecimento e cultura o aleitamento materno direcionadas a crianças escolares. Estudos de intervenção utilizando tecnologias educacionais (4) têm se mostrado eficazes para promover o conhecimento de estudantes escolares sobre aleitamento materno, a exemplo disso um estudo realizado no Recife (PE), com crianças do ensino fundamental utilizando uma tecnologia educacional do tipo jogo de tabuleiro, apresentou efeito positivo ao comparar o conhecimento sobre aleita-mento materno entre o grupo intervenção e o grupo controle.…”
Section: Introdução Sunclassified